Hal taerif man 'ana - Al Blooshi, Hamda; Jaber, Zainab (Sharjah, United Arab Emirates : Ashtar Publications, 2022)
Helping the child to get to know himself, and how to interact with the environment around him, so he can practice his hobbies, and it highlights the importance of the family
Keywords: Arabic language -- Readers -- Fiction; Children's stories, Arabic